Treatment of mutants as an allegory of the pathologization of subjects of non-intelligible genders: a reading from the x-men hq - Gonçalves, Fábio Mahal da Silva; Reina, Fábio Tadeu; Siqueira, Ranyella Cristina de; Carvalho, Marco Aurélio de (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
The characters of the comics have gained notoriety by transcending to the world of movies and television, especially the X-men. With great potential to reproduce perceptions and conceptions about the most different aspects of human life, the comics have served as a background for a reflection on social, cultural and moral issues. Having as a source of research the editions of 1 to 6 of the super gifted arc of the comics The incredible X-men, we will relate the pathology of the mutants of the comics as an allegory to the pathologization of sexual minorities, offering material for reflection and work for the respect to sexual diversity. Understanding the offer of the mutant cure as an allegory to the gay cure, we will reveal the underlying allegory in the condition of the characters in their fight against the pathologization of their mutant status, relating to the situation of the subjects of non-intelligible genders.